Tauroursodeoxycholic acid reduces apoptosis and protects against neurological injury after acute hemorrhagic stroke in rats - Rodrigues, CMP (2015)
Tauroursodeoxycholic acid (TUDCA), an endogenous bile acid, modulates cell death by interrupting classic pathways of apoptosis. Intracerebral hemorrhage (ICH) is a devastating acute neurological disorder, without effective treatment, in which a significan